Manajemen Bencana Dan Governance Mind Set - Jurnal Governance Jurnal Kebijakan & Manajemen Publik; Wima Yudho P; M. Chazienul Ulum (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2011)
In principle the the idea of writing this paper for mempertautkan two sides of the actual problem, namely the empirical problems associated with disaster management in Indonesia - including the problem of bureaucratic ethos in situations of disaster-related and theoretical sides of the application and development of governance models. So, how materialization of concepts and values of governance in the context of disaster management in the form of a synergistic network of inter-actor cooperation and mapping of roles and responsibilities of each party. In addition, development and environmental education within the framework of governance based disaster management is a necessity for sustainable environmental conservation.